Allergic cutaneous and visceral angioedema secondary to clozapine: A case report - Chia, LC; Md Rosli, Ahmad Nabil; M, Marhani; A, Muna Hamiza (Medical Research & Innovation Secretariat, Universiti Kebangsaan Malaysia Medical Centre, 2017)
This report stresses on the occurrence of a rare adverse reaction to clozapine, i.e. allergic cutaneous and visceral angioedema, in a patient with treatment resistant schizophrenia (TRS). We report the case of a schizophrenic patient who was resistant to treatment and developed an allergic reaction involving her skin and gastro-intestinal system upon the commencement of clozapine. She was then treated with a combination pharmacotherapy which left some residual symptoms. The manifestation of allergic reactions to clozapine and its management strategies are discussed in the paper. There is a pressing need to develop a new psychotropic which is on par with clozapine